Diseminasi Oleh Dokter Kecil tentang Penggunaan Hand Sanitizer Berbentuk Gel dan Spray untuk Menurunkan Angka Kuman Tangan Siswa SDN Demakijo I Di Gamping, Sleman, Yogyakarta - Ana Rida Diana; Lilik Hendrarini; Narto Narto (Poltekkes Kemenkes Yogyakarta, 2013)
Schools are educative institution whose function is for building, fostering and improving the qua-lity of human resources. The application of clean and healthy living behavior is very important to maintain the health of school aged children. One example of the application of that behavior is hand washing, nonetheless there are many schools that lack of hand washing facilities. Beside hand washing, hand sanitizer which has two types, i.e. gel and spray, is a material that can be used to reduce hand microbe number. The education on how to use the sanitizer among ele-mentary school students may be through their peer “little doctor”. This study was aimed to know the effect of information dissemination about hand sanitizer by the little doctor towards the de-crease of hand microbe number of SDN Demakijo I students in Gamping, Sleman. The study was an experiment which followed pre test and post test only design. There were 70 respon-dents who were sampled from grade III, IV and V of the school, and then they were divided into two groups so that each type of hand sanitizer had 35 respondents. The paired t-test yielded p values < 0,001 for both types of sanitizer, and therefore it was concluded that the two types significantly capable in reducing the microbe number. Furthermore, the independent t-test yield-ed a p value < 0,,001 which is meant that the microbe reduction between the two types was significantly different. Spray hand sanitizer was more effective because it was able to reduce 89,54 % of the microbe compared with only 69,90 % of the gel type.